Peran Pembiayaan Syariah dalam Mendukung Sertifikasi Halal Sebagai Upaya Peningkatan Daya Saing UMKM Kuliner di Kota Jambi - Desri Maulina; Ahmad Fansuri; Nailatussilmiyati Nailatussilmiyati; Paizah Rahmayeni; Riska Eviolina; Titin Agustin Nengsih; Novi Mubyarto (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to analyze the role of Islamic financing (pembiayaan syariah) in supporting the halal certification process and its impact on improving the competitiveness of culinary MSMEs in Jambi City. A descriptive qualitative method with a case study approach was employed, using in-depth interviews and observations of culinary MSME actors who have and have not obtained halal certification. The findings indicate that: (1) access to Islamic financing significantly assists MSME actors in covering halal certification costs; (2) halal-certified culinary MSMEs have broader market reach and higher consumer trust levels; (3) obstacles remain, including low Islamic financial literacy and complex halal certification administrative procedures. This study recommends synergy between Islamic financial institutions, BPJPH, and local government to create a conducive ecosystem for culinary MSMEs to obtain halal certification sustainably.